Deep-water bony fishes collected by the B/O Miguel Oliver on the shelf edge of Pacific Central America: An annotated, illustrated and DNA-barcoded checklist - Robertson, D. Ross; Angulo, Arturo [UNESP]; Baldwin, Carole C.; Pitassy, Diane; Driskell, Amy; Weigt, Lee; Navarro, Ignacio J.F. (Magnolia Press, 2017)
An annotated and photographically illustrated checklist with DNA barcodes of the species of bony fishes collected during a month-long research cruise of the Spanish Research vessel B/O Miguel Oliver is presented. The vessel made trawls on the continental shelf of the Pacific coast of Central America, in November-December 2010, at depths of 108-1625 m. This list, based on 707 specimens (of a total of 876 specimens collected during the whole expedition), includes 129 species belonging to 15 orders, 61 families, and 97 genera. New information is presented on the geographical distributions of more than a third of those species, with 29 species (22.4%) representing new records from Central American waters and 17 species (13.2%) having expanded latitudinal ranges. Data on capture depths demonstrate increased depth ranges due to new minimum and/or maximum known depths for 31 species, i.e. 24% of those captured. Tissue samples from frozen specimens were used to obtain DNA barcodes of 682 (96.5%) individuals belonging to 118 species (91.4% of those recorded here), which have been made publically available in Genbank. Those data include barcodes for 84 species (65.1% of the total collected, and 77.1% of those for which barcodes were obtained) and 30 genera (30.9% of those collected) for which no species barcodes have been previously published. Barcodes of 54 species represent the first genetic sequences of any type published for those species. The abundance of new data indicate that there is still much to learn about the composition and geographical and depth distributions of the fish fauna of the shelf edge and continental slope of this region.
Keywords: Deep sea; Diversity; Ichthyofauna; New records; Tropical eastern Pacific